Evaluasi Aliran Air Menggunakan Aplikasi HEC-RAS pada Saluran Primer di Kelurahan Kameloh Kota Palangka Raya - Yulindra, Dila; Respati, Rida; Saputra, Norseta Ajie (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The flood that occurred in Tumbang Nusa Village could have occurred due to high rainfall, intensity, or due to incorrect land use in the upstream area. In addition, floods can also be caused by climate change, disruption of the flow of rainwater in rivers, reduction of the surface area that absorbs water due to the construction of many buildings and the occurrence of forest destruction, overflow of the main rivers that pass through residential and urban areas, due to the intensity of rainfall. which is high in the upper reaches of the river which also often causes flooding. Based on the description above, efforts need to be made to anticipate flooding. Flow conditions in the Primary Canal of Kameloh Subdistrict, Palangka Raya City with flood discharge based on Nakayasu Hydrograph Synthetic Unit (HSS) for the Q2 year return period = 150,0 m3/sec and for the Q25 year return period = 221, 24 m3/sec. For forecasts for the next 2 years and 25 years based on simulations using the Hec-Ras application that the channel is still safe from flooding, it’s just that several station points have standing water on the left and right due to the low elevation.